The balance of adult mental health care: provision of core health versus other types of care in eight European countries. (2020) - Cetrano, G.; Salvador-Carulla, L.; Tedeschi, F.; Rabbi, L.; Gutiérrez-Colosía, M. R.; Gonzalez-Caballero, J. L.; Park, A.-L.; McDaid, D.; Sfetcu, R.; Kalseth, J.; Kalseth, B.; Hope, Ø.; et al.
Abstract: Aims: Although many mental health care systems provide care interventions that are not related to direct health care, little is known about the interfaces between the latter and core health care. 'Core health care' refers to services whose explicit aim is direct clinical treatment which is usually provided by health professionals, i.e., physicians, nurses, psychologists. 'Other care' is typically provided by other staff and includes accommodation, training, promotion of independence, employment support and social skills. In such a definition, 'other care' does not necessarily mean being funded or governed differently. The aims of the study were: (1) using a standard classification system (Description and Evaluation of Services and Directories in Europe for Long Term Care, DESDE-LTC) to identify 'core health' and 'other care' services provided to adults with mental health problems; and (2) to investigate the balance of care by analysing the types and characteristics of core health and other care services. Methods: The study was conducted in eight selected local areas in eight European countries with different mental health systems. All publicly funded mental health services, regardless of the funding agency, for people over 18 years old were identified and coded. The availability, capacity and the workforce of the local mental health services were described using their functional main activity or 'Main Types of Care' (MTC) as the standard for international comparison, following the DESDE-LTC system. Results: In these European study areas, 822 MTCs were identified as providing core health care and 448 provided other types of care. Even though one-third of mental health services in the selected study areas provided interventions that were coded as 'other care', significant variation was found in the typology and characteristics of these services across the eight study areas. Conclusions: The functional distinction between core health and other care overcomes the traditional division between 'health' and 'social' sectors based on governance and funding. The overall balance between core health and other care services varied significantly across the European sites. Mental health systems cannot be understood or planned without taking into account the availability and capacity of all services specifically available for this target population, including those outside the health sector.